Analysis Of The Influence Of Company Size And Corporate Governance Mechanism On Profit In Consumer Sector Manufacturing Companies Listed On The Indonesia Stock Exchange - Diandra Soraya; Puja Rizqy Ramadhan; Mika Debora Br. Barus (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
The purpose of this research is to provide empirical evidence of the affect of firm’s size, and corporate governance mechanisms on earnings. Firms size was measure by natural logaritma of net sales, and corporate governance mechanisms were measure by three variabels (composition of independent board commisioner, audit quality were measure by industry specialize audit firm, and composition of audit committee). Earnings was measure by net profit. The population of this research is 36 companies in the manufacturing firms focusly consumntion sector which were listed in Indonesian Stock Exchange (IDX). The research data were collected from manufacturing companies’ financial statement for the period of 2018 to 2020. Based on purposive sampling method, there are 16 samples. The reseacrh hypotesis were tested using multiple regression analysis. The results of this research show that firm size and composition of independent board commisioner have positive significant relationships with earnings and then simultaneously firm size and corporate governance mechanism have significant relationship with earning. Variable Auditors’ industry spesialization and composition of audit committee have no significant relationship with earnings.